2022
DOI: 10.1029/2021ef002335
|View full text |Cite
|
Sign up to set email alerts
|

Amplification Effect of Urbanization on Atmospheric Aridity Over China Under Past Global Warming

Abstract: While it is well known that rapid urbanization poses prominent effects on regional or local temperature changes under global warming, possible impacts of urbanization on the changes in atmospheric aridity (measured by vapor pressure deficit [VPD]) are poorly understood. In this study, we provide a national investigation of the spatiotemporal changes of atmospheric aridity over China in recent decades by analyzing observations at over 2,000 weather stations across China during 1971–2017 and further quantify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…(2015) also confirmed that about 80% stations in China experienced prominent increases for dry days (precipitation amount = 0) and decreases for trace days (0 < precipitation amount <0.1 mm/day). Such shift of precipitation from light to intense rainfall accompanied with the enhancement by the urbanization process may further give rise to the aggravation of drought events, which was consistent with the trend of light rainfall and drought shown in Figures 6a and 6b and 6e–6h (Wang et al., 2022a, 2022b, 2022c).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…(2015) also confirmed that about 80% stations in China experienced prominent increases for dry days (precipitation amount = 0) and decreases for trace days (0 < precipitation amount <0.1 mm/day). Such shift of precipitation from light to intense rainfall accompanied with the enhancement by the urbanization process may further give rise to the aggravation of drought events, which was consistent with the trend of light rainfall and drought shown in Figures 6a and 6b and 6e–6h (Wang et al., 2022a, 2022b, 2022c).…”
Section: Resultssupporting
confidence: 85%
“…For example, different from the other urban agglomerations, the heavy rainfall in both rural and urban regions of CY indicated a downward trend from 1981 to 2020. Previous studies confirmed that Western Pacific Subtropical High (WPSH), EAM, and South Asian Monsoon (SAM) exerted substantial effects on the heavy rainfall patterns of the eastern, central, and western Sichuan Basin, respectively (Hu et al., 2009; T. Gao et al., 2019; Wang et al., 2022a, 2022b, 2022c). Besides, due to the unique topography, locations, and complex interaction of diverse climate factors, urbanization showed less effects on the aggravation of drought in urban areas in GZ.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Note that wind speed can accelerate the airflow around the human body, speeding up the heat exchange between the human body surface and the air to play a cooling effect (Edwards et al, 2015;Roshan et al, 2020), so the wind speed in urban areas is reduced due to the impact of urbanization, which in turn leads to a higher local body temperature than the surrounding areas. The urbanization contribution to other HPT indicators without considering the effect of wind speed is generally smaller than that on air temperature, which may be related to the urban Frontiers in Environmental Science frontiersin.org dry island (UDI) effect due to urbanization, which may reduce the atmospheric humidity and thus offsetting the HPT increases to some extent (Hao et al, 2018;Luo and Lau, 2019;Huang et al, 2022;Wang et al, 2022). Table 2 summarizes the mean urban trend (T u ), rural trend (T r ), urbanization effect (UE), and urbanization contribution (UC) of the HPT under different seasons by averaging all HPT indicators.…”
Section: Long-term Changes In Mean Hpt and Urbanization Effectsmentioning
confidence: 99%